2006
DOI: 10.1002/cncr.21878
|View full text |Cite
|
Sign up to set email alerts
|

ACTIBIND, an actin‐binding fungal T2‐RNase with antiangiogenic and anticarcinogenic characteristics

Abstract: In view of the complexity of surface photografting polymerization of vinyl acetate/maleic anhydride (VAC/MAH) binary monomer systems, a novel method was adopted in the present article to obtain insight into the relevant grafting copolymerization mechanism. This method includes two steps: semibenzopinacol dormant groups were first introduced onto LDPE film by UV‐irradiation and then thermally reactivated to produce LDPE macromolecular free radicals, which initiated the grafting copolymerization of VAC and MAH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 118 publications
5
58
0
Order By: Relevance
“…We extracted a T 2 RNase from the fungus Aspergillus niger and established that it inhibits the elongation and alters the orientation of pollen tubes in plants by interfering with the intracellular actin network; thus, we named it ACTIBIND (9). More recently, we reported that ACTIBIND exerted preventive and therapeutic effects in two different models of colorectal cancer (10). Our results indicated that ACTIBIND may function as an antiangiogenic and antivascular drug, targeting tumor-associated blood vessels (10).…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations
“…We extracted a T 2 RNase from the fungus Aspergillus niger and established that it inhibits the elongation and alters the orientation of pollen tubes in plants by interfering with the intracellular actin network; thus, we named it ACTIBIND (9). More recently, we reported that ACTIBIND exerted preventive and therapeutic effects in two different models of colorectal cancer (10). Our results indicated that ACTIBIND may function as an antiangiogenic and antivascular drug, targeting tumor-associated blood vessels (10).…”
Section: Introductionmentioning
confidence: 55%
“…More recently, we reported that ACTIBIND exerted preventive and therapeutic effects in two different models of colorectal cancer (10). Our results indicated that ACTIBIND may function as an antiangiogenic and antivascular drug, targeting tumor-associated blood vessels (10). We postulated that ACTIBIND might exert its antiangiogenic activities through inhibition of angiogenin.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Actin was reported to bind to some of the T2/S-type RNase family proteins, such as human RNASET2 and Aspergillus ACTIBIND. E3 ligase, such as SLF in Plantaginaceae and SBP1 and SLF in Solananaceae, were also reported to bind to S-RNase (Hua and Kao, 2006;O'Brien et al, 2004;Qiao et al, 2004;Roiz et al, 2006;Sims and Ordanic, 2001;Smirnoff et al, 2006). Although E3 ligase homologs can be very good candidates for general inhibitors of S-RNase, we selected the actin homolog for further characterization in this study and left E3 ligase homologs for future studies, because we suspected that S-RNase may exert its cytotoxic effects through its actin-binding ability.…”
Section: Y2h Screening To Isolate Pollen Proteins Interacting With S-mentioning
confidence: 99%